Misuse of herbal teas - Simões, Deise Vimaana Santos de Souza; Freitas , João Fábio de; Silva , Abner Lucas Carvalho da (Seven Editora, 2024)
This literature review article addresses the "Misuse of Herbal Teas". We explore the traditional benefits of these teas, highlighting their long history of use in diverse cultures. We discuss the risks associated with inappropriate use, including side effects and drug interactions, as well as the lack of regulation in production and marketing. We emphasize the importance of guidance from healthcare professionals before consuming herbal teas and suggest strategies to educate the public about responsible use. This article highlights the need to balance the benefits and risks of these natural products and promote an informed approach to herbal medicine. DOI:https://doi.org/10.56238/sevened2024.007-043